Cross-Modal Correspondences Between Temperature and Taste Attributes - Motoki, Kosuke; Saito, Toshiki; Nouchi, Rui; Sugiura, Motoaki (Frontiers in Psychology, 2020)
Temperature is an important characteristic of food and drink. In addition to food-intrinsic temperature (i.e. serving temperature), consumers often experience food-extrinsic temperature (e.g. physical warmth). Emerging research on cross-modal correspondence has revealed that people reliably associate temperature with other sensory features. Building on the literature on cross-modal correspondence and sensation transference theory, the present study aimed to reveal mental representations of temperature–taste correspondence and cross-modal mental representations influencing corresponding sensory/hedonic perceptions of beverages, with a focus on manipulating food-extrinsic warmth. To reveal mental representations of temperature–taste correspondence, Experiment 1 investigated whether temperature words (warm, cool) are associated with sensory/hedonic attributes (e.g. sweet, sour, salty, bitter). The results of Experiment 1 demonstrated that warm (vs. cool) was matched more with saltiness, tastiness, healthfulness, and preference (intention to buy), whereas cool (vs. warm) was matched more with sourness and freshness. Experiment 2 assessed whether cross-modal mental representations influence corresponding sensory/hedonic perceptions of beverages. The participants wore hot and cold pads and rated sensory/hedonic attributes of Japanese tea (Experiment 2a) or black coffee (Experiment 2b) before and after tasting it. The results of Experiment 2a demonstrated that physical warmth (vs. coldness) increased healthfulness and the intention to buy Japanese tea. The results of Experiment 2b did not reveal any effects of physical warmth on sensory/hedonic ratings. These findings provide evidence of taste–temperature correspondence and provide preliminary support for the influence of food-extrinsic warmth on taste attributes related to positivity.